Command-Line Cartographic Data Processing for Geophysical Plotting of Rwanda Using GMT and R Scripts - (:unkn) unknown (My University, 2022)
This paper presents a case of the script-based cartographic data processing by the Generic Mapping Tools (GMT) and R language for geophysical mapping. The study area is located in Rwanda, Africa, which is notable for complex geological setting due to its specific location within the East African Rift. The active continental zone of the East African Rift extending in western Rwanda has importance on seismicity of the country. It affects gravity anomaly and influences the distribution and shape of the geomorphological landforms, as reflected in the topography of Rwanda. The aim of this study is to apply the cartographic command-line techniques for mapping. The geophysical goal is to highlight the correlations between the distribution, depth and magnitudes of earthquakes, topography and geophysics. Visualizing the geophysical anomalies and topography for the morphometric setting of Rwanda's terrain supports geological monitoring. The data include the General Bathymetric Chart of the Oceans (GEBCO), Earth Gravitational Model of 2008 (EGM2008), satellite derived gravity and the Shuttle Radar Topography Mission (SRTM). Nine new thematic maps on Rwanda are presented and evaluated to demonstrate the influence of the East African Ridge on regional distribution of the earthquakes and volcanos in Rwanda. The maps demonstrated accurate and effective mapping achieved due to the functionality of R and GMT scripts. A regional analysis shows that the distribution of the earthquakes and volcanoes is the highest in the western part of Rwanda and the lowest in the east proving the correlation of the active seismicity with the tectonic setting and geology of the country. The console-based scripts of R and GMT are presented with provided link to the author's GitHub repository with a full access to the codes.
Keywords: African Research